Does Traditional Islamic Malay Literature Contain Shi‘itic Elements? ‘Ali and Fātimah in Malay Hikayat Literature - Wieringa, Edwin (Studia Islamika, 1996)
Many experts of classical Malay literature argues that Persian influence is known very well to the traditional Malay literature. This is evident from a number of Malay literary texts are very popular, such as Saga Bakhtiar, Hikayat Amir Hamzah, Hikayat Muhammad Hanafiyah and The Book of the Thousand Known issues is a kind of adaptation or translation even langsungdari Persian texts. Key issue of this paper is wanted to be appointed; whether there is influence in the Persian classical Malay literature was once an indication of the influence of Shiite against Sunni Islam which evolved from the beginning of the archipelago?DOI: 10.15408/sdi.v3i4.795